2007
DOI: 10.1529/biophysj.106.090472
|View full text |Cite
|
Sign up to set email alerts
|

Nematode Sperm Motility: Nonpolar Filament Polymerization Mediated by End-Tracking Motors

Abstract: In nematode sperm cell motility, major sperm protein (MSP) filament assembly results in dynamic membrane protrusions in a manner that closely resembles actin-based motility in other eukaryotic cells. Paradoxically, whereas actin-based motility is driven by addition of ATP-bound actin subunits onto actin filament plus-ends located at the cell membrane, MSP dimers assemble from solution into nonpolar filaments that lack a nucleotide binding site. Thus, filament polarity and on-filament ATP hydrolysis, although e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It can be concluded that K01G5.3 may have a more direct role than ENU-3 and C38D4.1 in modification of the cytoskeleton with a possible role in actin interaction and modulation. It is likely that they are involved in regulating actin formation and turnover similar to the functions of characterized membraneassociated proteins such as fascin, N-WASP and the Arp 2/3 complex (Dickinson & Purich, 2007). This is indicative of the expression pattern of K01G5.3 which showed several thin, finger-like structures protruding from the cell similar to filopodia which consist of actin filaments cross-linked by actin-binding proteins (Hanein, Matsudaira, & DeRosier, 1997).…”
Section: Enu-3 and Its Paralogs May Have Roles In Cytoskeletal Rearrangementmentioning
confidence: 92%
“…It can be concluded that K01G5.3 may have a more direct role than ENU-3 and C38D4.1 in modification of the cytoskeleton with a possible role in actin interaction and modulation. It is likely that they are involved in regulating actin formation and turnover similar to the functions of characterized membraneassociated proteins such as fascin, N-WASP and the Arp 2/3 complex (Dickinson & Purich, 2007). This is indicative of the expression pattern of K01G5.3 which showed several thin, finger-like structures protruding from the cell similar to filopodia which consist of actin filaments cross-linked by actin-binding proteins (Hanein, Matsudaira, & DeRosier, 1997).…”
Section: Enu-3 and Its Paralogs May Have Roles In Cytoskeletal Rearrangementmentioning
confidence: 92%
“…More recently, biochemical kinetics that regulates the biophysical processes of force generation has been incorporated in a model [970]. Besides, an alternative plausible scenario of MSP assembly has been proposed [971] to explain the motility of nematode sperm cells.…”
Section: •Force Generated By Depolymerizing Msp In Nematodesmentioning
confidence: 99%
“…But, contrary to ATP-driven actin treadmilling, MSPs assemble into apolar filaments and lack a nucleotide binding site for ATP hydrolysis. To power membrane protrusion, it has recently been proposed that motor end-tracking proteins processively polymerize MSP filaments, while keeping the elongating filaments' ends in contact with membrane-associated proteins [177]. For cell progression however, a second force is required, namely a traction force that pulls the cell body forward once the advancing lamellipodium has been anchored to the substrate on which the cell is crawling.…”
Section: E Another Example Of Filament-driven Amoeboid Motility: the ...mentioning
confidence: 99%